KINERJA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA BATAM - Solikha, Jamiatus; Dompak, Timbul (SCIENTIA JOURNAL, 2021)
This research aims to identify the performance of the Population and Civil Registration Agency of Batam especially in implementing the effectiveness and the efficiency of public service of Electronic ID Card (e-KTP). Data shows the obstacles in public service of e-KTP such as the number of blank e-KTP are still lack, allegations of maladministration, suspicion of prolonged delays in issuing e-KTP. It also reported on the Top Three category of public services cases in Batam in 2019. This research uses qualitative methods with a descriptive approach. Data collected by using direct interviews, direct observation and documentation (books and journals) and uses Spradley method by determining the key informants continued by interviewing and completed by reporting. The results of this study conclude that the performance of the Population and Civil Registration Agency of Batam is good but still need improvements for better public service, especially for e-KTP. It is assessed based on Dwiyanto's performance indicator theory, such as productivity, service quality, responsiveness, responsibility, accountability and Pasolong’s theory that describe the factors that influence the performance of public organizations such as ability, willingness, energy, technology, compensation, clarity of objectives, and security.